The Role of Good Governance Toward Economic Growth of Riau Province - Y Rahmat Akbar; Resti Riandi (AFEBI Economic and Finance Review, 2021)
This study aims to analyze the effect of good governance on regional financial performance and allocation of capital expenditures and their impact on economic growth in districts and cities in Riau Province. The research was conducted quantitatively with a causal and descriptive research design. The population in this study were 12 districts and cities in Riau Province. Data samples were obtained from the Revenue Service and the Regional Financial and Asset Management Office of Riau Province. The research was carried out by census on budget realization reports from 2016 to 2020 so that 60 data were obtained. The data analysis technique used was Partial Least Square (PLS) analysis. The results of this study indicate that good governance has a significant effect on regional financial performance and allocation of capital expenditures. Regional financial performance has a significant effect on the allocation of capital expenditures and does not have a significant effect on economic growth. Direct capital expenditure allocation has no significant effect on economic growth. Indirectly, good governance has a significant effect on economic growth through regional financial performance and allocation of capital expendituresThis study aims to analyze the effect of good governance on regional financial performance and allocation of capital expenditures and their impact on economic growth in districts and cities in Riau Province. The research was conducted quantitatively with a causal and descriptive research design. The population in this study were 12 districts and cities in Riau Province. Data samples were obtained from the Revenue Service and the Regional Financial and Asset Management Office of Riau Province. The research was carried out by census on budget realization reports from 2016 to 2020 so that 60 data were obtained. The data analysis technique used was Partial Least Square (PLS) analysis. The results of this study indicate that good governance has a significant effect on regional financial performance and allocation of capital expenditures. Regional financial performance has a significant effect on the allocation of capital expenditures and does not have a significant effect on economic growth. Direct capital expenditure allocation has no significant effect on economic growth. Indirectly, good governance has a significant effect on economic growth through regional financial performance and allocation of capital expenditures